Clinical Diagnosis - Chiarelli, Catherine (Canadian Journal of Optometry, 2021)
C.W., a 7-year-old male, presented with his parents for another opinion, seeking treatment to improve binocularity. He had been under the care of an ophthalmologist since age 4 years. At that time, glasses were prescribed to correct a right esotropia. Occlusion therapy also was recommended, and was done consistently for several months. Two years ago, bifocal lenses were prescribed to further improve eye alignment. At a recent follow-up, C.W and his parents were told that visual acuity and the esotropia were adequately corrected with bifocals, and that no further treatment was required. Annual follow-up was advised.